15‐Deoxy‐Δ12, 14‐prostaglandin J2 (15d‐PGJ2) protects neurons from oxidative death via an Nrf2 astrocyte‐specific mechanism independent of PPARγ. (3rd January 2013) - Haskew‐Layton, Renée E.; Payappilly, Jimmy B.; Xu, Hongbin; Bennett, Steffany A. L.; Ratan, Rajiv R.
Abstract Astrocytes are critical for the antioxidant support of neurons. Recently, we demonstrated that low level hydrogen peroxide (H2O2) facilitates astrocyte‐dependent neuroprotection independent of the antioxidant transcription factor Nrf2, leaving the identity of the endogenous astrocytic Nrf2 activator to question. In this study, we show that an endogenous electrophile, 15‐deoxy‐Δ12, 14‐prostaglandin J2 (15d‐PGJ2), non‐cell autonomously protects neurons from death induced by depletion of the major antioxidant glutathione. Nrf2 knockdown in astrocytes abrogated 15d‐PGJ2's neuroprotective effect as well as 15d‐PGJ2 facilitated Nrf2‐target gene induction. In contrast, knockdown of the transcription factor peroxisome proliferator activated‐receptor gamma (PPARγ), a well‐characterized 15d‐PGJ2 target, did not alter 15d‐PGJ2 non‐cell autonomous neuroprotection. In addition, several PPARγ agonists of the thiazolidinedione (TZD) family failed to induce neuroprotection. Unexpectedly, however, the TZD troglitazone (which contains a chromanol moiety found on vitamin E) induced astrocyte‐mediated neuroprotection, an effect which was mimicked by the vitamin E analogs alpha‐tocopherol or alpha‐tocotrienol. Our findings lead to two important conclusions: (i) 15d‐PGJ2 induces astrocyte‐mediated neuroprotection via an Nrf2 but not PPARγ mediated pathway, suggesting that 15d‐PGJ2 is a candidate endogenous modulator of Nrf2 protective pathways in astrocytes; (ii) selective astrocyte treatment with analogs or compounds containing the chromanol moiety of vitamin E facilitates non‐cell autonomous neuroprotection.